Decision to invest in Islamic unit trust fund: evidence of employee provident fund (EPF) contributors - Imad, Oussedik Mohamed (2018)
Despite the effort by the Employee Provident Fund (EPF) to promote investment in the Members Investment Scheme (MIS), the EPF members’ investment is still low. Hence, increasing the EPF members’ investment is a major challenge. A few studies have used the Theory of Planned Behaviour (TPB) to identify the factors influencing the intention and the investment decision of EPF contributors. This study aimed to fulfil this gap by investigating the TPB variables (attitude, subjective norm, and perceived behavioural control) with additional variables (religiosity and social ethical environmental concern) on investment intention and decision. This investigation employed the multistage sampling for data collection to solicit responses from 330 EPF members. Using the Partial Least Square Structural Equation Modelling (PLSSEM), the extended model explains 72 percent of the total variance in intention. Attitude, subjective norm, perceived behavioural control and religiosity are found to have positive and significant influences on intention except social ethical environmental concern. Using intention as a mediator, the model explains 67 percent of the variation in the investment decision. Furthermore, the result suggested that intention positively and significantly mediates the relationships between attitude, subjective norm, perceived behavioural control and religiosity, and investment decision. Several implications emerged from these empirical findings. First, the study highlighted the role of intention in investment decision. Therefore, EPF needs to create a strong intention by developing positive members’ attitude towards Islamic unit trust investment, peer and family references, and Shariah compliance, besides providing additional information that may facilitate EPF members’ investment decision. Second, the investigation offered insightful information to the EPF, as the policy -maker, on the investment decision of its members. In conclusion, the findings of PLS-SEM support the application of the TPB theory to enhance investment decision within the context of retirement investment in Malaysia.